Ancient Israel what do we know and how do we know it? - Grabbe, Lester L. 1945- (London Bloomsbury Publishing PLC, 2017)
Cover -- Half-Title -- Title -- Copyright Page -- Dedication -- Contents -- Abbreviations -- Preface to the Second Edition -- Preface to the First Edition -- Part I: Introduction -- Chapter 1: The Principles and Methods of Investigating the History of Ancient Israel -- 1.1 Aims -- 1.2 Concepts and Complications: The Question of Sources and Methods -- 1.2.1 The Place of the Social Sciences -- 1.2.2 The Longue Durée -- 1.2.3 The Model and Method of Classical Studies -- 1.2.4 Using Archaeology as a Source -- 1.2.4.1 General Comments -- 1.2.4.2 Terminology of Archaeological Periods -- 1.2.4.3 Use of Survey Data -- 1.2.4.4 The Debate Over the 'Low Chronology' -- 1.2.4.5 Estimating Population -- 1.2.4.6 The Stratigraphy of Samaria -- 1.2.4.7 Reinterpretation of the Jochan Seal -- 1.2.4.8 Problems with Forgeries -- 1.2.5 Ethnicity -- 1.2.6 Ideology and Neo-Fundamentalism -- 1.2.7 'Maximalists', 'Minimalists' and the ad hominem Argument -- 1.3 The Contemporary Practice of Writing Israel's History -- 1.3.1 Developments in General Historiography -- 1.3.2 Forty Years of Debate Among Biblical Scholars -- 1.3.3 Principles of Historical Method Used in this Book -- Part II: Historical Investigations -- Chapter 2: Second Millennium: Middle and Late Bronze Ages (2000-1300 BCE) -- 2.1 Sources -- 2.1.1 Archaeology -- 2.1.2 Egyptian Texts -- 2.1.2.1 Execration Texts -- 2.1.2.2 Amarna Letters -- 2.1.2.3 The Story of Sinuhe -- 2.1.3 Ugaritic Texts -- 2.1.4 Mesopotamian Texts -- 2.1.5 Biblical Text -- 2.2 Analysis -- 2.2.1 Peoples/Ethnic and Social Groups -- 2.2.1.1 Hyksos -- 2.2.1.2 Amorites (Amurru) -- 2.2.1.3 'Apiru/Ḫaberu -- 2.2.1.4 Shasu (Shosu, Š3św, Sutu) -- 2.2.1.5 Canaanites -- 2.2.2 Question of the Patriarchs -- 2.3 Synthesis -- 2.3.1 First Part of Second Millennium (ca. 2000-1600/1500 BCE) -- 2.3.1.1 Egypt.
2.3.1.2 Old Assyrian Period (ca. 2000-1750) -- 2.3.1.3 Old Babylonian Period (2000-1600) -- 2.3.1.4 Hittites -- 2.3.1.5 Northern Syria -- 2.3.2 Second Part of the Second Millennium (1600/1500-1200 BCE) -- 2.3.2.1 Egypt -- 2.3.2.2 Mesopotamia -- 2.3.2.3 Hittite Empire (ca. 1400-1200 BCE) -- 2.3.2.4 Mitanni Kingdom (ca. 1600-1350 BCE) -- 2.3.2.5 Ugarit -- 2.3.3 Palestine -- Chapter 3: Late Bronze to Iron IIA (ca. 1300-900 BCE): From Settlement to Statehood -- 3.1 Sources -- 3.1.1 Archaeology -- 3.1.1.1 Analysis -- 3.1.2 Merenptah Stela -- 3.1.3 Medinet Habu and Related Inscriptions -- 3.1.4 Report of Wenamun -- 3.1.5 Shoshenq I's Palestinian Inscription -- 3.1.6 Biblical Text -- 3.1.6.1 Pentateuch -- 3.1.6.2 Deuteronomistic History (DtrH) -- 3.2 Analysis -- 3.2.1 The Question of the Exodus -- 3.2.2 The Sea Peoples and the Philistines -- 3.2.2.1 The Coming of the Sea Peoples -- 3.2.2.2 The Development of the Philistines -- 3.2.3 Transjordan -- 3.2.4 From Settlement to Statehood -- 3.2.4.1 Joshua and Judges -- 3.2.4.2 The Settlement -- 3.2.4.3 'Tribes' and 'Nomads' -- 3.2.4.4 Anthropological Models of Statehood -- 3.2.4.5 The Early Monarchy: Saul, Samuel, David, and Solomon Traditions -- 3.2.5 Writing, Literacy and Bureaucracy -- 3.3 Synthesis -- Chapter 4: Iron IIB (900-720): Rise and Fall of the Northern Kingdom -- 4.1 Sources -- 4.1.1 Archaeology -- 4.1.2 Hebrew Inscriptions -- 4.1.3 Aramaic Inscriptions -- 4.1.3.1 Tel Dan -- 4.1.3.2 Melqart Inscription -- 4.1.3.3 Zakkur Inscription -- 4.1.4 Mesha Stela -- 4.1.5 Assyrian Sources -- 4.1.6 Phoenician History of Menander of Ephesus -- 4.1.7 Biblical Text -- 4.1.7.1 1 Kings 16.15-2 Kings 17.41 (2 Chronicles 18-28): Outline of the Contents -- 4.1.7.2 Analysis -- 4.2 Analysis -- 4.2.1 Dividing of the Kingdom (1 Kings 12-14)
4.2.2 Rulers of Judah and Israel to Omri (1 Kings 15.1-16.20) -- 4.2.3 Ahab -- 4.2.4 Israel and Moab -- 4.2.5 The Aramaeans -- 4.2.6 From Jehu to the End of the Northern Kingdom (2 Kings 9-16) -- 4.2.7 Fall of Samaria -- 4.2.8 Development of Religion -- 4.2.8.1 The God Yhwh -- 4.2.8.2 Other Deities and Worship -- 4.2.8.3 Temple Religion versus 'Popular'/'Folk'/'Family' Religion -- 4.2.8.4 Development of Monotheism -- 4.3 Synthesis -- 4.3.1 Biblical Data Confirmed -- 4.3.2 Biblical Data Not Confirmed, Though They May Be Correct -- 4.3.3 Biblical Picture Incorrect -- 4.3.4 Biblical Picture Omits/has Gaps -- Chapter 5: Iron IIC (720-539 BCE): Peak and Decline of Judah -- 5.1 Sources -- 5.1.1 Archaeology -- 5.1.1.1 Conclusions with Regard to Archaeology -- 5.1.2 Palestinian Inscriptions -- 5.1.2.1 The Adon Papyrus -- 5.1.2.2 Meṣad Ḥashavyahu -- 5.1.2.3 Arad Ostraca -- 5.1.2.4 Lachish Letters -- 5.1.2.5 The Ashyahu Ostracon -- 5.1.2.6 Seals and Bullae -- 5.1.3 Assyrian Sources -- 5.1.3.1 Sargon II (721-705 BCE) -- 5.1.3.2 Sennacherib (705-681 BCE) -- 5.1.3.3 Esarhaddon (681-669 BCE) -- 5.1.3.4 Ashurbanipal (669-627 BCE) -- 5.1.4 Babylonian Sources -- 5.1.4.1 Nabopolassar (626-605 BCE) -- 5.1.4.2 Nebuchadnezzar II (605-562 BCE) -- 5.1.4.3 Jehoiachin Documents -- 5.1.4.4 Texts from āl-Yāhūdu and Našar -- 5.1.5 Egyptian Source: Psammetichus Inscription -- 5.1.6 The Biblical Story: 2 Kings 21-25 and Parallels -- 5.1.6.1 2 Kings//2 Chronicles -- 5.1.6.2 Jeremiah -- 5.1.6.3 Ezekiel -- 5.1.6.4 Ezra -- 5.1.6.5 Daniel -- 5.1.6.6 Analysis of the Text -- 5.2 Analysis -- 5.2.1 Hezekiah -- 5.2.2 Manasseh -- 5.2.3 Amon -- 5.2.4 Josiah -- 5.2.5 Jehoahaz -- 5.2.6 Jehoiakim -- 5.2.7 Jehoiachin -- 5.2.8 Zedekiah -- 5.2.9 The Case of Jeremiah -- 5.2.10 The Case of Nebuchadnezzar -- 5.2.11 The 'Exile' -- 5.3 Synthesis
5.3.1 Biblical Data Confirmed -- 5.3.2 Biblical Data Not Confirmed, Though They May Be Correct -- 5.3.3 Biblical Picture is Most Likely Incorrect -- 5.3.4 Biblical Picture Omits/Has Gaps -- Part III: Conclusions -- Chapter 6: 'The End of the Matter': What Can We Say about Israelite and Judahite History? -- Bibliography -- Index of References -- Index of Authors -- Index of Subjects
Keywords: Electronic books